DIGITALISATION OF EDUCATION: UNLIMITED INNOVATION IN THE MODERN LEARNING ERA - Opi Irawansah; Muhalida Zia Ibhar (Adisam Publisher, 2025)
This study discusses the transformation of the education system through digitalisation, which brings unlimited innovation in the era of modern learning. The digitalisation of education enables broader, more flexible, and personalised access to learning by utilising technologies such as Learning Management Systems (LMS), interactive media, and learning analytics. However, the digitisation process is not without significant challenges, such as infrastructure inequality, teacher readiness, data security issues, and psychological impacts on students. This study uses qualitative methods with literature review to identify strategic solutions that can overcome these obstacles, including infrastructure equalisation, teacher digital competency training, security regulation development, and the implementation of hybrid learning models. The results of this study are expected to provide recommendations for education stakeholders in optimising digital innovation to create an inclusive, adaptive, and sustainable education system.